THE ROLE OF JOB TRAINING IN IMPROVING THE PERFORMANCE OF ATBM WEAVING EMPLOYEES PT. ASAPUTEX TEGAL CITY - Riyanto, Fery; Ingsih, Kusni (Jurnal Manajemen dan Dinamika Bisnis (JMDB), 2023)
The purpose of this study was to determine the effect of job training on the competency and performance of ATBM weaving employees of PT Asaputex Tegal City. The population in this study were all employees of PT Asaputex Tegal City totaling 135 employees. The sampling technique used in this study is the census technique. The research method used is quantitative, using the Structural Equation Model (SEM) using AMOS 26 software. The results show that 1) Job training has an indirect effect on the performance of employees of PT Asaputex Kota Tegal through competency as mediation, 2) Work training has a direct effect on the performance of employees of PT Asaputex Tegal City.Keywords: job training; competency; employee performance